Editorial - Anna Oksiutycz (Communicare)
In this issue, we have revived a tradition which I was reminded of when looking through some of Communicare’s past issues, dating back to the 1980s, now uploaded to the open-access site. In the early days, Communicare’s very lively 'Last Word' slot invited critical comments on contemporary matters of concern, but for the most part, the journal took a hands-off position and followed conventional publishing practice.